Emergence of Cochin in the pre-industrial era : a study of Portuguese Cochin - Mathew, Kuzhippalli Skaria, 1939-; Ahmed, Afzal, 1954-; Pondicherry University (Pondicherry : Pondicherry University, 1990)
Chiefly documents.
Includes bibliographical references (p. 143-149) and index.
Introduction in English, documents in Portuguese.
Keywords: Cochin (India) -- History -- Sources